New relational understandings of city building: Reading the city through dynamic landscapes of spatial governance - Tasan-Kok, Tuna (AESOP, 2021)
In this think piece I will take you on a journey to share my approach to reading contemporary city building, which is increasingly chaotic, fragmented, and complex. Spatial governance, in my understanding, refers to the collective efforts to coordinate and structure the dynamic institutional activities of a variety of actors that aim to organise the built environment. Urban planning is one of these efforts, though not the only one. Therefore, in this article, I will visualise spatial governance as a dynamic landscape which accommodates multi-actor, multi-scalar, multi-loci and multi-temporal regulatory activities related to the uncertainties, opportunities, and crises of the market. Reading dynamic landscapes of spatial governance requires an understanding of regulatory efforts as they refer to the relational behaviour of state, market, and community actors. This approach, to linking regulatory efforts to relational behaviour, in my view, gives us new opportunities to provide comprehensive understandings of how cities develop under market-driven conditions.
Transactions of the Association of European Schools of Planning; Volume 5 / Issue 1 / June 2021; page 1-8